The decision to adopt internet-based e-commerce: An empirical analysis based on Swiss firm-level data - Heinz Hollenstein; Martin Wörter (ETH Zurich, KOF Swiss Economic Institute, 2004)
The paper aims at explaining empirically the diffusion of E-commerce based on two largescale sample surveys conducted in the Swiss economy. The paper adds to previous work in two ways: firstly, we estimate separate models for E-selling and E-purchasing, and, secondly, we distinguish between inter-firm diffusion (i.e. technology adoption) and intra-firm diffusion (i.e. intensity of technology use). It turns out that the pattern of explanation strongly differs between the two types of E-commerce as well as the two types of diffusion. Therefore, further studies dealing with the diffusion of E-commerce should differentiate along these two dimensions. Besides, it is shown that institutional, technological and economic uncertainty as well as adjustment costs, which are neglected in most studies of diffusion, are important explanatory variables. Moreover, it turned out that rank effects are clearly more important drivers of adoption and intra-firm diffusion of the two types of E-commerce than epidemic effects, which are of some importance only in case of adoption.
Keywords: L2; O31; O33; 330; Technology diffusion; Inter- vs. intra-firm diffusion; E-commerce; E-selling vs. E-purchasing; Information and Communication Technologies (ICT); Rank and epidemic effects of diffusion; E-Business; Informationstechnik; Innovationsdiffusion; Schätzung; Schweiz